Clinical and Ergonomic Comparison Between a Robotic Assisted Transfer Device and a Mobile Floor Lift During Caregiver-Assisted Wheelchair Transfers. (30th June 2022) - Greenhalgh, Mark; Blaauw, Eline; Deepak, Nikitha; St Laurent, Matthew; Cooper, Rosemarie; Bendixen, Roxanna; Grindle, Garrett G.; Koontz, Alicia M.; Cooper, Rory A.
Abstract : Background: The robotic assisted transfer device was developed as an updated lift technology to reduce adjustments in posture while increasing capabilities offered by transfer devices. The purpose of this study was to compare the trunk biomechanics of a robotic assisted transfer device and a mechanical floor lift in the transfer of a care recipient by a caregiver during essential transfer tasks. Methods: Investigators enrolled 28 caregiver/care recipient dyads to complete 36 transferring tasks. Surface electromyography for the back muscles and motion data for trunk range of motion were collected for selected surfaces, phase, and direction tasks using a robotic assisted transfer device and a mechanical floor lift. Results: Robotic assisted transfer device transfers required significantly smaller range of trunk flexion ( P < 0.001), lateral bend ( P < 0.001), and axial rotation ( P = 0.01), in addition to smaller distance covered ( P < 0.001), average instantaneous velocity ( P = 0.01), and acceleration ( P < 0.001) compared with a mobile floor lift. The robotic assisted transfer device transfers required significantly smaller peak erector spinae (left: P = 0.001; right: P < 0.001) and latissimus dorsi (right: P < 0.001) and integrated erector spinae left ( P = 0.001) and latissimus dorsi right ( P = 0.01) electromyography signals compared with the floor lift. Conclusions: The robotic assisted transfer device provides additional benefits to mobile floor lifts which, coupled with statistically lower flexion, extension, and rotation, may make them an appealing alternative intervention.